The Black community and bodily autonomy : where do we go from here? - King, Nykaysia (East Carolina University, 2022)
Through this thesis I sought to add to the literature regarding the influence of pervasive police brutality on young Black people. In it I explore the relationship between police brutality and influence on Black people's bodily autonomy by gender, gender identity, and sexuality. Through the lenses of Afro-Pessimism and Intersectionality, I find that the pervasive culture of police violence influences the bodily autonomy of young Black people. This influence varies by gender, gender identity, and sexuality, mirroring the policing of Black people's bodies throughout history. As such, I advocate for structural change in policing such that young Black people can self-autonomize and self-actualize as full human beings whose lives matter and have independent meaning.
Keywords: Agency; Black Queer People; Black people--Social conditions; Police brutality; Right to bodily autonomy; Black lives matter movement